Respuesta :

Answer:

-8

Step-by-step explanation:

+16-16=0

-(-24)+12-(+36)=0

So +16-(-24)+(-8)-16+(12)-(+36)=-8

Answer: -8

Step-by-step explanation:

Given expression

16 - (-24) + (-8) - 16 + (12) - (36)

Expand parentheses and change signs when [-] sign is in front

=16 + 24 - 8 - 16 + 12 - 36

Combine all the terms through addition/subtraction

=40 - 8 - 16 + 12 - 36

=32 - 16 + 12 - 36

=16 + 12 - 36

=28 - 36

=[tex]\boxed{-8}[/tex]

Hope this helps!! :)

Please let em know if you have any questions